Representasi Kecantikan Perempuan Pada Kampanye Be Your Own Melalui YouTube BLP Beauty - Karinia Cantika Putri; Retno Dyah Kusumastuti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
Women are closely related to beauty. The beauty of women has always been a matter of discussion in society. Therefore, a beauty stigma is formed in society which becomes a demand for women to look beautiful. This has encouraged BLP Beauty to take great opportunities in advertising its products as well as creating a Be Your Own themed campaign to build women's confidence in being beautiful. Women's beauty no longer has to follow the stigma of women's beauty that develops in society. To get an understanding of the contents of the message behind the advertising campaign, a semiotic study is needed to find the message behind the Be Your Own advertising campaign. This study uses a qualitative approach in a descriptive form and uses John Fiske's semiotic content analysis method. The results of the analysis of this study indicate that the representation of women's beauty displayed in the Be Your Own advertising campaign by BLP Beauty is that beauty is to be yourself.